Providing Eye Gaze Interaction for Ginga-NCL Applications - Montevecchi, Eyre Brasil B.; Josué, Marina I. P.; Barreto, Fábio; Abreu, Raphael S. de; Muchaluat-Saade, Débora C. Muchaluat (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2020: Proceedings of the 26th Brazilian Symposium on Multimedia and the Web, 2020)
Eye-tracking sensors allow users to interact by eye gaze with multimedia applications, providing a new interaction modality for those who do not want or cannot use the traditional ones (mouse, keyboard, and remote control). Considering digital TV applications, middleware Ginga-NCL does not support this type of interaction yet. In this paper, we propose a Ginga-NCL extension to provide eye-gaze interaction using eye-tracking technology and enable the use of a new event type for NCL multimedia authoring, called EyeGaze.